The role of comorbidieites in the prognosis of thermal burns - Abhinav Aggarwal; Ravi Kumar Chittoria; Vinayak K Chavan; Saurabh Gupta; Chirra Likhitha Reddy; Padmalakshmi Bharathi Mohan; Imran Pathan; K Shijina (Wolters Kluwer Medknow Publications, 2019)
Context: Burn injury is a complex trauma with multiple changes in physiology of the patient. Assessing prognosis of the burn patient is a subject of debate with various prognostic scores available. The presence of inhalational injury and percentage (total body surface area) of thermal burns are the most important factors affecting the outcome of the burn patient. The role of comorbidities is another very important factor and its importance cannot be undermined, especially with massive fluid shifts associated with resuscitation and body catabolism in the rehabilitative stage, respectively. Charlson Comorbidity Index (CCI) is an attractive scale that has stood the test of time as a scale to measure objectively the severity of comorbidities on the prognosis. Aims: The aim of the study was to understand the role of comorbidities have on the outcome of thermal burns. Materials and Methods: This was a retrospective analysis of burn patients admitted in the burns center over the past 1 year fulfilling the inclusion criteria. Descriptive analysis of patient records was done. Results: A total of 18 patients with comorbidities admitted in the burns center fulfilling the above-said inclusion criteria. Ten patients survived, while eight patients succumbed to the burn injuries. The average CCI of the survivor group was 2.2 (range: 1-4), whereas the mean CCI of the nonsurvivor group was 3.5 (range: 2-6). Conclusion: Comorbidities do have an impact on the prognosis of a burn patient, and objective assessment of prognosis of the burn injury must include the CCI as a tool to predict the outcome correctly and reliably.